2017
DOI: 10.1038/s41598-017-11144-w
|View full text |Cite
|
Sign up to set email alerts
|

A new red cell index and portable RBC analyzer for screening of iron deficiency and Thalassemia minor in a Chinese population

Abstract: Anemia is a widespread public health problem with 1/4 ~1/3 of the world’s population being affected. In Southeast Asia, Thalassemia trait (TT) and iron deficiency anemia (IDA) are the two most common anemia types and can have a serious impact on quality of life. IDA patients can be treated with iron supplementation, yet TT patients have diminished capacity to process iron. Therefore, distinguishing between types of anemia is essential for effective diagnosis and treatment. Here, we present two advances towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…Red blood cell distribution width (RDW) is another important CBC parameter. RDW has been used for the diagnosis and differential diagnosis of various types of anemia . In recent years, changes in RDW have been found to be related to the inflammatory state of the body, which has been shown to affect the development of tumors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Red blood cell distribution width (RDW) is another important CBC parameter. RDW has been used for the diagnosis and differential diagnosis of various types of anemia . In recent years, changes in RDW have been found to be related to the inflammatory state of the body, which has been shown to affect the development of tumors .…”
Section: Introductionmentioning
confidence: 99%
“…RDW has been used for the diagnosis and differential diagnosis of various types of anemia. 15 In recent years, changes in RDW have been found to be related to the inflammatory state of the body, 16,17 which has been shown to affect the development of tumors. 18,19 Therefore, researchers explored the relationship between RDW and the prognosis of some malignant tumors and confirmed that a high RDW is associated with a poor prognosis, such as in breast cancer, 20 esophageal cancer, 21 non-small cell lung cancer (NSCLC), 22 SCLC, 23 and other tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The zero degree scattering is defined by the propagation direction of the incident beam, while our optical system collects the forward-directed portion of the 4π-steradian sphere of scattering angles. Compared to our prior-reported system, 35 the utilized wavelengths have been changed, and the optical system has been redesigned to eliminate a dichroic mirror, reducing cost while minimizing wavefront aberrations that can interfere with the generation of a clean scattering pattern.…”
Section: Elastic Light Scattering Systemmentioning
confidence: 99%
“…33,34 We previously reported that quadratic discriminant analysis (QDA) applied to the three red cell parameters MCV, RDW, and MCHC outperformed established indices in discriminating healthy from anemic patients, and IDA from TT patients in Chinese children. 35 However, these parameters are currently measured in the hospital by a complex flow cytometry system that requires regular maintenance and operation by a highly trained user. This makes their measurement by standard methods unsuitable for wide-spread population-level screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation